The impact of Arab Spring Revolutions on the purposes of Islamic Sharia - Abdulghani, Naser Ali Edrees (Journal of Islamic Sciences, 2021)
This research aims to study the impact of the Arab Spring revolutions on the purposes of Sharia. I relied on the descriptive analytical method in writing this research, and it contained three sections, and I touched upon the effects of revolutions on the purpose of protection of Life, Lineage, and Intellect, also, I talked about the purpose of protection of religion in terms of moral values in the light Arab Spring. And this study also discussed the economic effects of the revolutions on the spring countries and their neighboring countries as well.After researching the effects of the Arab Spring, I concluded that the deterioration of the security and political conditions had a negative impact on various aspects of the religious, social and economic life of the countries of the Spring, and the purposes of Sharia are to preserve the reasons for which the revolutions took place, and that the Arab Countries Threatened with division due to the spread of sectarian and terrorist movements, as well as civil wars.
Keywords: Islamic Sharia; Arab Spring; Impact; Purposes; revolutions